The Effect of the Combination of Dysmenorrhea Gymnastics and Warm Compresses with Warm Water Zak on Reducing the Intensity of Dysmenorrhea Pain - Minarti Minarti; Nurmalaya Farzana Silmi; Sari Luthfiyah; Joko Suwito; Aini Ahmad (International Journal of Advanced Health Science and Technology, 2025)
A common problem experienced by almost all women of childbearing age is dysmenorrhea. This is caused by hormonal changes as well as factors such as unhealthy lifestyle, smoking, and family history. The conjunction of dysmenorrhea gymnastics and warm compresses has been demonstrated to effectively reduce the intensity of pain. This study seeks to investigate the impact of the combination of dysmenorrhea gymnastics and warm compresses alongside Warm Water Zak (WWZ) on alleviating the intensity of dysmenorrhea pain among level 4 students enrolled in the Bachelor of Applied Nursing program. The research methodology employed was quasi-experimental, utilizing a pretest-posttest design paired with a nonequivalent control group design. Sampling was conducted through probability sampling, specifically employing the simple random sampling method, resulting in a total of 32 samples distributed across four groups. The research instruments utilized included a Numeric Rating Scale (NRS) pain questionnaire, Standard Operating Procedures (SOP) for dysmenorrhea gymnastics and warm compresses with WWZ, observation sheets, and informational leaflets. The statistical assessment of normality was performed using the Shapiro-Wilk test wilk. A multivariate analysis was conducted employing the One-Way ANOVA Test and Bonferroni's post hoc test. The results of the One-Way ANOVA test indicate a significance value of 0.000, which is less than 0.050. Furthermore, the Bonferroni post hoc test results reveal a significant difference (p < 0.05) across several groups. This finding demonstrates that the combination of dysmenorrhea gymnastics and warm compresses with warm water zak (WWZ) has a notable effect on reducing the intensity of dysmenorrhea pain among level 4 students of the Bachelor of Applied program Nursing.